"Ain't about the money, ain't about the haircut": Experiences of servant leadership in black-owned barbershops and beauty salons during the COVID-19 pandemic - Hunter M. Boehme; Robin M. Dawson; Tameka Williams; Lídia Gual-Gonzalez; Chloe Rodriguez-Ramos; Natalie Brown; Bryceson Hernandez; Lekendra Kidd; Melissa S. Nolan (Elsevier, 2023)
The COVID-19 pandemic had a disproportionate, negative effect on Black Americans. Black-owned barbershops/beauty salons are traditionally trusted, yet little is known regarding how these "virtue locales" were affected by the pandemic. This theory-guided, qualitative descriptive study explored owners' experiences in addressing their clients' and community well-being during the first pandemic year, revealing four emergent themes: 1) "blessings" and cultural expectations informed a moral imperative to become servant leaders, 2) long-standing relationships resulted in opportunities to engage on topics of physical and mental health, 3) Barbershop/beauty salon-based COVID-19 information and resources led to individual and community empowerment, and 4) Barbershops and beauty salons were "virtue locales", or physical manifestations of social responsibility and psychological safety during the pandemic. These results support that these locations are trusted spaces where health issues can be discussed, and that their owners are willing and trusted community leaders that can be leveraged to implement culturally appropriate health interventions.